Hydraulic and Hydrologic Modeling of Steep Channel of Putih River, Magelang District, Central Java Province, Indonesia - Adi Putri Anisa Widowati (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2017)
Hydrologic and hydraulic modeling are important to be conducted to examine the watershed response based on a rainfall input, especially over disaster-prone watershed such as Putih River watershed in Magelang, Central Java Province. A GIS-based grid-based distributed rainfall-runoff model was used to simulate the rainfall-runoff transformation. A two-dimensional hydrodynamic flow modeling was then carried out to simulate the flood processes on the stream and floodplain area. A sensitivity analysis was conducted on infiltration rate, Manning’s n value, and rainfall intensity. Infiltration rate, Manning’s n value, and rainfall intensity give considerable effects to the resulted flow hydrographs. The modeling results show that the results of hydrologic-hydraulic modeling is in good agreement with the observed results.